Moana [videorecording (DVD)] (Disney, 2017)
A mythic adventure set around 2,000 years ago across a series of islands in the South Pacific. The film follows the journey of a spirited teenager named Moana as she meets the once-mighty demi-god Maui, and together they traverse the open ocean, encountering enormous fiery creatures and impossible odds.